Surveilans Status Gizi Balita Usia 0-59 Bulan Di Kabupaten Magetan Provinsi Jawa Timur - Handayani, Dwi (JOURNAL OF Community Health Issues, 2025)
Background: The health of children under five years of age is a crucial factor for the survival of future generations. Therefore, continuous assessment of the nutritional status of toddlers is crucial to determine their nutritional status. Purpose: To determine the nutritional status of toddlers aged 0-59 months in Magetan Regency, East Java Province. Method: This study was a quantitative descriptive study. The population was all 28,239 toddlers in Magetan Regency. The sampling technique used was accidental sampling. The sample size was 584 toddlers. Data were taken from the 2023 Indonesian Health Survey (SKI). Data were collected using questionnaires and anthropometric measurements. Data were analyzed using univariate and bivariate chi-square tests. Results: The nutritional status of toddlers aged 0-59 months was assessed based on age/weight and age/height. The majority had normal weight and height. Conclusion: There is a relationship between weight and height in the nutritional status of toddlers in Magetan Regency. Suggestion: Maintaining the health, growth, and development of toddlers is expected to always involve Posyandu cadres, namely by increasing the role of Posyandu cadres in monitoring the nutritional status of toddlers and in providing nutritional education to the community, and actively involving the community in health and nutrition programs and forming mother support groups to share information and experiences regarding child nutrition. Keywords: Maternal Support; Nutritional Status; Toddler Pendahuluan: Kesehatan anak di bawah usia lima tahun adalah faktor penting untuk kelangsungan hidup generasi mendatang, sehingga penilaian status gizi balita penting dilakukan secara berkelanjutan untuk mengetahui status gizi balita. Tujuan: untuk mengetahui gambaran status gizi balita usia 0-59 bulan di Kabupaten Magetan Provinsi Jawa Timur. Metode: Jenis penelitian ini adalah penelitian deskriptif kuantitatif. Populasi dalam penelitian ini yaitu semua balita yang berada di kabupaten Magetan bejumlah 28.239 balita. Tehnik pengambilan sampel dalam penelitian ini yaitu dengan Accidental Sampling. Jumlah sampel dalam penelitian ini yaitu 584 balita.data diambil dari hasil Survei Kesehatan Indonesia(SKI) tahun 2023. Data diambil dengan mengumpulkan menggunakan kuesioner dan hasil pengukuran antopometri. Data di analisis dengan univarat dan bivariate Chi-Square. Hasil: Status gizi pada balita usia 0-59 ditinjau berdasarkan umur/berat serta umur/tinggi badan badan mayoritas memiliki berat badan dan tinggi badan normal. Simpulan: Ada hubungan berat badan dengan tinggi badan pada status gizi balita di Kabupaten Magetan. Saran: Mempertahankan kesehatan, pertumbuhan, dan perkembangan balita maka diharapkan dapat selalu melibatan kader posyandu, yaitu dengan meningkatkan peran kader posyandu dalam pemantauan status gizi balita dan dalam memberikan edukasi gizi kepada masyarakat, dan libatkan masyarakat secara aktif dalam program-program kesehatan dan gizi serta membentuk kelompok-kelompok dukungan ibu untuk saling berbagi informasi dan pengalaman mengenai nutrisi anak. Kata Kunci: Balita; Dukungan Ibu; Status Gizi